To evaluate antioxidant, cytotoxic, antibacterial activities of aerial parts ethanol extracts from Nepeta sibirica L. grown in Mongolia - Ayurzana, Amarjargal; Batbayar, Bayarkhuu; Jambal, Irekhbayar; Shatar, Altantsetseg; Chultem, Oyuntsetseg (IJRDO-Journal of Applied Science, 2020)
: Mongolia is rich in medicinal plants. In recent years, interest in plant-derived food additives has grown. Many Lamiaceae species have a characteristic scent or taste, which in many cases are the reason for their application in Mongolian traditional medicine. This study was aimed to evaluate antioxidant, cytotoxic activities of aerial parts ethanol extracts from Nepeta sibirica L. grown in Mongolia. The antioxidant and cytotoxic activities of the essential oil and ethanol crude extracts were determined by using DPPH and MTT assays. The ethanol extracts showed higher antioxidant activity than essential oil. The results clearly showed that the essential oil presented satisfactory cytotoxic activity against two human tumor cell lines HepG2 (human liver cancer cell line); AGS (human stomach cancer cell line). Our work revealed that the ethanol extracts and essential oil of Nepeta sibirica L. grown in Mongolia has potential as sources of new antioxidant, and cytotoxic compounds, respectively.